Infestation of a diabetic foot by Wohlfahrtia magnifica - José M. Villaescusa, MD; Itziar Angulo, MD; Alejandro Pontón, MD, PhD; J. Francisco Nistal, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2016)
Myiasis is the infestation of animals or humans by larvae from some species of dipteran flies. Depending on the tissues invaded, the maggots of these insects can produce different diseases of the skin, or mucoses (ocular, genitourinary, and oropharyngeal). Wohlfahrtia magnifica is one of the species causing myiasis; although it is a real veterinary problem, it rarely infests humans and extraordinarily in the context we describe. We herein present the case of a diabetic patient diagnosed with class IV peripheral vascular disease (Fontaine classification) who suffered infestation by W. magnifica and the management given to this pathologic process. The patient consented to the publication of this report.